2019
DOI: 10.1161/circep.119.007465
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Ablation of TASK-1 (Tandem of P Domains in a Weak Inward Rectifying K + Channel–Related Acid-Sensitive K + Channel-1) (K 2P 3.1) K + Channels Suppresses Atrial Fibrillation and Prevents Electrical Remodeling

Abstract: Background: Despite an increasing understanding of atrial fibrillation (AF) pathophysiology, translation into mechanism-based treatment options is lacking. In atrial cardiomyocytes of patients with chronic AF, expression, and function of tandem of P domains in a weak inward rectifying TASK-1 (K + channel–related acid-sensitive K + channel-1) (K 2P 3.1) atrial-specific 2-pore domain potassium channels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…Pigs were treated with an adeno-associated viral vector carrying anti-TASK-1-siRNA which was injected in both atria and led to a reduced expression of TASK-1. This treatment led to a prolongation of the APD and reduction of TASK-1 current in the siRNA group compared to AF control pigs and to a significant reduction in AF burden (Schmidt et al, 2019b). Liang et al (2014) showed that loss-of-function mutations of TASK-1 lead to increased susceptibility to develop AF in the presence of pro-arrhythmic stimuli and Harleton et al (2015Harleton et al ( , 2013 observed a phosphorylation dependent TASK-1 dysregulation in a canine model of AF, further underlining its role in AF.…”
Section: Task-1 In Atrial Fibrillationmentioning
confidence: 95%
“…Pigs were treated with an adeno-associated viral vector carrying anti-TASK-1-siRNA which was injected in both atria and led to a reduced expression of TASK-1. This treatment led to a prolongation of the APD and reduction of TASK-1 current in the siRNA group compared to AF control pigs and to a significant reduction in AF burden (Schmidt et al, 2019b). Liang et al (2014) showed that loss-of-function mutations of TASK-1 lead to increased susceptibility to develop AF in the presence of pro-arrhythmic stimuli and Harleton et al (2015Harleton et al ( , 2013 observed a phosphorylation dependent TASK-1 dysregulation in a canine model of AF, further underlining its role in AF.…”
Section: Task-1 In Atrial Fibrillationmentioning
confidence: 95%
“…78 Genetic suppression of TASK-1 (Tandem of P Domains in a Weak Inward Rectifying K+ Channel-Related Acid-Sensitive K+ Channel-1; K2P3.1) through transfection of AAV containing atrial anti-TASK-1 siRNA lead to reduction of expression of TASK-1 and prolongation of atrial APD and refractoriness. 79 Ca 2+ handling proteins Abnormal sarcoplasmic reticulum (SR) Ca 2+ leak via the ryanodine receptor type 2 (RyR2) has been described in atrial cardiomyocytes from AF patients and in various AF models. 80,81 This disruption in calcium handling contributes to ectopic atrial activity and is implicated in the progression from paroxysmal to persistent AF.…”
Section: Ion Channelsmentioning
confidence: 99%
“…In a preclinical trial with an AF pig model, inhibition of atrial-specific K 2P 3.1 current using the TASK-1 channel blocker A293 reverses pathologic AF-related atrial action potential shortening and significantly prolongs atrial ERP without causing ventricular arrhythmias (Wiedmann et al, 2020). In another more recent pig preclinical trial, K 2P 3.1 current inhibition by genetic ablation of TASK-1 channels using small interfering RNA (siRNA) prevents atrial electrical remodeling and suppresses AF (Schmidt et al, 2019). However, an important caveat is that in chronic-AF patients with heart failure due to left ventricular dysfunction, atrial K 2P 3.1 expression is downregulated instead of upregulated, making it unlikely for I K2P blockers to be an efficient anti-AF approach in patients with structurally remodeled atria (Schmidt et al, 2017).…”
Section: K2p Blockers (A293 Doxapram)mentioning
confidence: 99%
“…For example, the Controlled Study of Rate vs. Rhythm Control in Patients with Chronic AF and Heart Failure (CAFÉ-II) found that the rhythm-control strategy, even when achieved by an antiarrhythmic drug such as amiodarone, was associated with greater symptomatic relief and improved quality of life as compared to the rate-control strategy ( Shelton et al, 2009 ).…”
Section: Evolving Therapeutic Strategiesmentioning
confidence: 99%